Decreased A20 expression on circulating CD56bright NK cells contributes to a worse disease status in patients with ankylosing spondylitis. (30th June 2019) - Yang, M; Zhou, Y; Liu, L; Wang, S; Jiang, J; Shang, Q; Yu, H; Xiang, X; Pang, X; Li, T; Zhao, P
Summary: A20, a pivotal anti-inflammatory protein, preserves immune homeostasis and regulates prolonged inflammation. A previous study has shown that A20 expression levels are down-regulated in peripheral blood mononuclear cells (PBMCs) from patients with ankylosing spondylitis (AS). However, the precise role of A20 in reducing autoimmune disorders needs to be further elucidated. In this study, A20 expression was found to be preferentially reduced on circulating CD56 bright natural killer (NK) cells in patients with AS, and its level was negatively correlated with that of proinflammatory cytokines. Further investigation demonstrated that A20 reduces interferon (IFN)-γ and tumour necrosis factor (TNF)-α production in CD56 bright NK cells after stimulation with monokines or phorbol myristate acetate (PMA)/ionomycin(P/I). Furthermore, CD56 bright NK cells isolated from AS patients promote TNF-α secretion by autologous monocytes, and increasing the A20 expression level partially attenuates this process. More importantly, decreased A20 expression on circulating CD56 bright NK cells is associated with worse disease status in patients with AS. Our findings reveal that A20 participates in the pathogenesis of AS by negatively regulating CD56 bright NK cells and that its reduced expression contributes to a worsened disease status in patients with AS. Graphical Abstract: